The Study of Surface Defects of Carbon Fibre Reinforced Polymer (CFRP) using Minimum Quantity Lubricant (MQL) in the Milling Process - Cheah, Chang Chong; bin Abd Rahim, Erween (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In recent years, the applications of composite materials are expanding widely due to the excellent physical and chemical properties which can replace the metal material. One of the commonly used composites are Carbon Fiber Reinforced Polymer (CFRP) due to its superior mechanical properties such as high strength-to-weight ratio, high stiffness-to-weight ratio and high corrosion resistance when compared to metal-based material. CFRP are frequently used in many areas, include the aerospace, military, automotive, construction, sport and even household appliances. However, machining of CFRP are always the challenging tasks due to its anisotropic, inhomogeneous, and abrasive nature which increase the difficulty of machining. Generally, the lower machined quality of CFRP is obtained during dry machining condition due to the induced defects caused by high cutting temperature. In this study, we are focusing on the investigation of the induced surface defects on CFRPs after end milling process by implementing Minimum Quantity Lubricant (MQL) and cutting tools with different geometries. In addition, the determination of proper cutting parameters and cutting tool geometries in achieving optimum machining performance on CFRP workpieces also been conducted. Machining performance was evaluated based on cutting force, surface roughness, effects of different cutting tool geometries, induced damages, and delamination factors. Cutting parameters with lower feed rate and higher spindle speed were effective in enhancing the machining performance due to the reduction of cutting forces, material removal rate, and tool wear. In addition, lower helix angled end mills with high number of flutes were recommended to prevent the delamination on CFRPs. Although, high cutting temperature occurred by increasing spindle speed due to plastic deformation of matrix material once it surpasses the glass-transition temperature, Tg (114-122℃). Implementation of MQL is proved to be effective to overcome these issues without providing excessive cooling effects when compared to cryogenic conditions.